THE INFLUENCE OF COUNTRY OF ORIGIN ON CONSUMER ATTITUDE TOWARD PURCHASE INTENTION OF LAPTOPS IN MANADO - Tantri, Anjeling (FEB Universitas Sam Ratulangi Manado, 2013)
Country of origin is a determinant of consumer attitude and purchase intention. Nowadays, people often discuss about country of origin, the place where the product is produced, where the product comes from, where the product is assembled and designed. It is hard to know exactly what the country of origin is. Consumer tend to use country of origin more as a decision tool when they make decision to purchase or when they purchase a product. The purpose of this research is to determine the influence of the country of origin to consumer attitude, the influence of attitude to purchase intention, and the influence of country of origin to purchase intention. Theories supporting this research are consumer behaviour, country of origin, consumer attitude and purchase intention. The population observed is people who have laptop or want to purchase laptop with the sample size as many as 200 respondents. This research is a quantitative analysis which uses the Structural Equation Model (SEM) analysis, IBM® SPSS® Amos™ 21.0 software to analyse the data. Results and conclusions are country of origin has a significant influence to consumer attitude. Furthermore consumer attitude has a strong significant influence to purchase intention. However, the analysis result has no prove to show the influences of country of origin on purchase intention. Keywords: country of origin, consumer attitude, purchase intention